4-Hexylphenol influences adipogenic differentiation and hepatic lipid accumulation in vitro. (1st January 2021) - Sun, Zhendong; Cao, Huiming; Liu, Qian S.; Liang, Yong; Fiedler, Heidelore; Zhang, Jianqing; Zhou, Qunfang; Jiang, Guibin
Abstract: Finding the potential environmental obesogens is crucial to explain the prevalence of obesity and the related pathologies. Increasing evidence has showed that many chemicals with endocrine disrupting effects can disturb lipid metabolism. Whether 4-hexylphenol (4-HP), a widely-used surfactant and a potential endocrine disrupting chemical (EDC), is associated to influence adipogenesis and hepatic lipid accumulation remained to be elucidated. In this study, both the 3T3-L1 differentiation model and oleic acid (OA)-treated HepG2 cells were used to investigate the effects of 4-HP on lipid metabolism, and the underlying estrogen receptor (ER)-involved mechanism was explored using MVLN assay, molecular docking simulation and the antagonist test. The results based on lipid droplet staining and triglyceride accumulation assay showed that 4-HP treatment promoted the adipogenic differentiation of 3T3-L1 cells and increased hepatic cellular OA accumulation in exposure concentration-dependent manners. The study on the elaborated transcription networks indicated that 4-HP activated peroxisome proliferator-activated receptor γ (PPARγ) as well as the subsequent adipogenic gene program in 3T3-L1 cells. This chemical also induced the increase of OA uptake and decreases of de novo lipogenesis and fatty acid oxidation in HepG2 cells. The agonistic activity of 4-HP in triggering ER-mediated pathway was shown to correlate with its perturbation in lipid metabolism, as evidenced by the enhanced development of mature lipid-laden adipocytes and suppression of excessive hepatic lipid accumulation upon its co-treatment with ER antagonist. Altogether, these findings provide new insights into the potential health impacts of 4-HP exposure as it may relate to obesity and nonalcoholic fatty liver disease. Graphical abstract: Image 1 Highlights: 4-HP promoted adipogenic differentiation and cellular lipid accumulation in 3T3-L1 cells. 4-HP upregulated expressions of PPARγ and adipogenesis biomarkers in differentiated adipocytes. 4-HP increased lipid deposition in OA-treated HepG2 cells. 4-HP altered expressions of genes related to lipid uptake, de novo lipogenesis and fatty acid oxidation in HepG2. 4-HP could potentially increase incidence of obesity and nonalcoholic fatty liver disease.